O braku demokracji w edukacji dla demokracji - pozory, zniewolenie i trudne poszukiwanie zmiany = About the lack of democracy in education for democracy - semblances, servitude and difficult search for changes - Olczak, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
One of the key tasks facing education in a democratic society is to prepare citizens to function in a constantly changing reality. This raises the question of whether one can prepare citizens for life in a democratic society and fully understand the mechanisms of democracy without practicing democracy from childhood?
Keywords: demokracja; pozory; zniewolenie; dzieciństwo; democracy; semblance; servitude; childhood